ANALISIS NILAI PENDIDIKAN KARAKTER DALAM NOVEL SIE PO GIOK KARYA TIO IE SOEI - Sinaga, Tio Novaria; Effendy, Chairil; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe analysis research of the character education values in novel Si Po Giok by Tio Ie Soei was a research that showed the values of character of the character in the novel. The character education on this research focused on the eighteen character values that were mentioned by Kemdikbud. This research also used the descriptive method and qualitative method. The resource in this research was novel Si Po Giok by Tio Ie Soei. The data from this research were a quotation of words, phrases, sentences, statements, and expressions in the novel that was related by the values of character. The analysis data were started by reading the data that have been tested for the validity, analyze descriptively to find the values of character in the novel, and made the implementations plan to the literary learning in High School. The results of the analysis showed that there were 15 values of character education in novel Sie Po Giok by Tio Ie Soei. The values of character education consist of religious, honest, tolerant, disciplined, hardworking, independent, democratic, curiosity, national spirit, respect for achievement, communicative, peace-loving, likes to read, carrying socially, and responsibility. The lesson plan of the novels learning in High School can be carried out in grade XI odd semester.Keyword: The character education, Novel